THE LIFE OF IMAM AL-BUKHARI AND HIS CONTRIBUTION TO THE DEVELOPMENT OF ISLAMIC SCIENCE (Modern education and development, 2025)
This article discusses the life of the great scholar of hadith, Imam al-Bukhari, his great contribution to the science of hadith, the scholar’s role and significance in the development of Islamic science. It also analyzes the role of his works in the science of hadith today.